Talking Stick Cooperative Learning Model To Improve Student Activity And Results In Sociology - Hasan Asyhari (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2023)
The learning model can support a learning process. However, teachers often pay little attention to this. So that among others resulted in active learning and student learning outcomes. The subjects of this study were Sociology teachers and students of class XI IPS 2 at SMAN 1 Buru. This type of research is Classroom Action Research (CAR), which consists of two cycles. The Classroom Action Research Model according to Kurt Lewin consists of two cycles. Each cycle has four stages, namely planning, implementing, observing, and reflecting. The research subjects were students of class XI IPS 2 at SMAN 1 Buru for the 2022/2023 academic year, with a total of 26 students. Data collection techniques used are observation, documentation and tests. Data were analyzed using qualitative analysis techniques. Based on the results of the study, it showed an increase in student learning activity seen in pre-action activities (pre-cycle) the percentage obtained was 19%, the percentage obtained in cycle I was 38%, the percentage obtained in cycle II was 54%. Then, the use of the talking stick type of cooperative learning model can also improve the learning outcomes of class XI IPS 2 SMAN 1 Buru in Sociology subjects. This can be seen from the increase in the average score that has been obtained starting from before the action or pre-action, then there is action in cycle I and cycle II. If in pre-action activities the average score obtained was 66 with a completeness percentage of 42%, cycle I obtained an average score of 74 with a completeness percentage of 58% and cycle II the average value obtained was 82 with a completeness percentage of 77%. In cycles I and II, seeing the activity and student learning outcomes increased according to the researcher's target. So it can be concluded that the cooperative learning model of the talking stick type in the Sociology subject of class XI IPS 2 SMAN 1 Buru can increase the activity and learning outcomes of students in class XI IPS 2 SMAN 1 Buru.